Evolving the Preconception Health Framework: A Call for Reproductive and Sexual Health Equity. Issue 2 (February 2021) - Dehlendorf, Christine; Akers, Aletha Y.; Borrero, Sonya; Callegari, Lisa S.; Cadena, Denicia; Gomez, Anu Manchikanti; Hart, Jamie; Jimenez, Laura; Kuppermann, Miriam; Levy, Barbara; Lu, Michael C.; Malin, Kiko; et al.
Abstract : Over the past decade, increasing attention has been paid to intervening in individuals' health in the "preconception" period as an approach to optimizing pregnancy outcomes. Increasing attention to the structural and social determinants of health and to the need to prioritize reproductive autonomy has underscored the need to evolve the preconception health framework to center race equity and to engage with the historical and social context in which reproduction and reproductive health care occur. In this commentary, we describe the results of a meeting with a multidisciplinary group of maternal and child health experts, reproductive health researchers and practitioners, and Reproductive Justice leaders to define a new approach for clinical and public health systems to engage with the health of nonpregnant people. We describe a novel " Reproductive and Sexual Health Equity " framework, defined as an approach to comprehensively meet people's reproductive and sexual health needs, with explicit attention to structural influences on health and health care and grounded in a desire to achieve the highest level of health for all people and address inequities in health outcomes. Principles of the framework include centering the needs of and redistributing power to communities, having clinical and public health systems acknowledge historical and ongoing harms related to reproductive and sexual health, and addressing root causes of inequities. We conclude with a call to action for a multisectoral effort centered in equity to advance reproductive and sexual health across the reproductive life course. Abstract : Maternal and child health experts, reproductive health researchers and practitioners, and Reproductive Justice leaders collaboratively developed a novel framework to advance equity in reproductive and sexual health.